1991
DOI: 10.1017/s0025315400051638
|View full text |Cite
|
Sign up to set email alerts
|

Deep Demersal Fish Assemblage Structure in the Porcupine Seabight (Eastern North Atlantic): Slope Sampling By Three Different Trawls Compared

Abstract: The demersal ichthyofauna of the continental slope of the Porcupine Seabight, eastern North Atlantic, was studied from 144 samples taken by three different types of otter trawl. At least 118 species from 43 families were represented among some 54,000 specimens collected from 247 to 2172 m soundings. Collectively, the catches were dominated in species richness by the Macrouridae, Alepocephalidae and Squalidae and in abundance by the Synaphobranchidae, Macrouridae and Moridae. Separately, relative abundance of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
100
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(108 citation statements)
references
References 13 publications
6
100
2
Order By: Relevance
“…They are usually found at bathyal depths, often with a wide depth range. However, no overlap was observed with the upper/mid-slope species, except for the predominating species on the lower slope of Ampère, Synaphobranchus kaupii, which has been reported, for example, from Porcupine Seabight at depths from 230 to 2,420 m (Merrett et al 1991).…”
Section: Discussionmentioning
confidence: 79%
“…They are usually found at bathyal depths, often with a wide depth range. However, no overlap was observed with the upper/mid-slope species, except for the predominating species on the lower slope of Ampère, Synaphobranchus kaupii, which has been reported, for example, from Porcupine Seabight at depths from 230 to 2,420 m (Merrett et al 1991).…”
Section: Discussionmentioning
confidence: 79%
“…Species richness decreases progressively from the upper slope down to about 2000 m depth (Haedrich et al, 1980;Pearcy et al, 1982;Gordon and Duncan, 1985). In the case of abundance, an exponential decrease with depth has been described by several authors (Grassle et al, 1975;Cohen and Pawson, 1977;Merrett and Domanski, 1985;Gordon, 1986;Merrett et al, 1991), although a stable tendency below a depth of 500 m seems to occur in the Mediterranean (Stefanescu et al, 1993;Moranta et al, 1998). The most important feature for fish biomass is the existence of a peak at intermediate depths of 800 and 1500 m depending on the areas surveyed (Marshall and Merrett, 1977;Gordon and Duncan, 1985;Gordon, 1986).…”
Section: Introductionmentioning
confidence: 93%
“…Body mass is a fundamental attribute of any animal and has an additional interest because most biological processes are scaled to the size of the organism (Peters, 1983). The analysis of size distributions in deep-sea fish studies focuses mainly on size depth relationships both for individual species and for the whole fauna (Haedrich and Rowe, 1977;Polloni et al, 1979;Merrett and Marshall, 1981;Sulak, 1982;Pearcy et al, 1982;Carney et al, 1983;Mauchline and Gordon, 1984;Middleton and Musick, 1986;Gordon and Duncan, 1987;Macpherson and Duarte, 1991;Merrett et al, 1991;Stefanescu et al, 1992). The causes pointed out by these authors to explain changes of size with depth are related mainly to food availability, interor intra-specific competition and predation.…”
Section: Introductionmentioning
confidence: 99%
“…11, see S T in May, 1975). Rank-abundance diagram was little known for offshore demersal fishes, but the species abundance histograms reported in some deep-sea ichthyofaunal studies (Merrett and Marshall, 1981;Merrett and Domanski, 1985;Merrett et al, 1991) also showed truncated lognormal patterns. The dominance of the first ranked species of our study (55% by number, 74% by weight) was higher than those of some works on European demersal fisheries data (Brander, 1988), in the slope off Morocco (Merrett and Marshall, 1981;Merrett and Domanski, 1985), and in the slope off Tasmania (May and Blaber, 1989), but various values were reported in North Atlantic deep waters (e.g., Snelgrove and Haedrich, 1985;Gordon and Duncan, 1985;Gordon and Bergstad, 1992;Merrett, 1992); the dominance was variable due to not only faunal characteristics but also the sample size, and direct comparison to other works seems rather difficult.…”
Section: Discussionmentioning
confidence: 99%
“…May and Blaber (1989) and Blaber et al (1990) used different catchabilities according to the species. Some combination of different trawls was also used for more accurate ichthyofaunal studies in the deep sea (Gordon and Duncan, 1985;Merrett et al, 1991;Gordon and Bergstad, 1992).…”
Section: Discussionmentioning
confidence: 99%